Legal Consequences of Presidential Decree Number 12 of 2020 on the Implementation of Private Contracts - Cendhani, Cindy; Elvi Kusuma Putri, Dita; Tambunan, Ezra (Universitas Negeri Semarang, 2020)
Corona Virus Disease 2019 (Covid-19) designated as National Disaster by Presidential Decree Number 12 of 2020 concerning Determination of Non-Natural Disasters for the Spread of Covid-19 (Keppres 12/2020). The determination of National Disaster resulted in public speculation would be used as basis canceling all types of contracts or being able to delay implementation contractual with argument force majeure. Force majeure provisions refer to articles 1244-1245 Burgerlijk Wetboek (BW). The question that arises is whether the determination of national disaster can be used as a reason for force majeure for all types of contracts and the legal consequences. This paper uses a normative legal research method with 3 (three) approaches, namely statute approach, conceptual approach, and case approach. So it can be concluded that the National Disaster in Keppres 12/2020 cannot automatically qualify as force majeure on all types of contracts. Because, in the Covid-19 a implementation private contracts still possible.